2021
DOI: 10.56874/jeel.v2i1.403
|View full text |Cite
|
Sign up to set email alerts
|

Teaching English Through Zoom Video Conferencing: Some Efl Teachers’ Experiences

Abstract: This article attempts to explore the EFL teachers’ experiences in using zoom video conferencing platform as the technological massive changes during remote learning in the pandemic situation. The research question is how EFL teachers’ experience in the perception toward zoom video conferencing platform. The aims are to know EFL teachers’ experience toward zoom video conferencing platform in the perception of its usefulness, ease of use and satisfaction during the zoom video session. The design of this study is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…The results concluded that all participants decided the internet connection was the teachers' chief obstacle when implementing the LV application. The results of this study support Sanjaya et al (2021), who affirms that teachers also face the same challenges, such as the internet connection when they are using the Zoom application to teach English, particularly teachers who live in remote place where the connection or signal is poor and unstable. As a result of the development of learning technology media, teachers must be more innovative and imaginative in their teaching to provide the best solutions when confronted with various obstacles.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The results concluded that all participants decided the internet connection was the teachers' chief obstacle when implementing the LV application. The results of this study support Sanjaya et al (2021), who affirms that teachers also face the same challenges, such as the internet connection when they are using the Zoom application to teach English, particularly teachers who live in remote place where the connection or signal is poor and unstable. As a result of the development of learning technology media, teachers must be more innovative and imaginative in their teaching to provide the best solutions when confronted with various obstacles.…”
Section: Discussionsupporting
confidence: 80%
“…Furthermore, several studies have investigated teachers' perspectives on using MALL applications to support the English teaching and learning process. Quizizz (Lim & Yunus, 2021); WhatsApp (Nsabayezu et al, 2020;Suryana et al, 2021); Kahoot (Nguyen & Yukawa, 2019); Zoom (Sanjaya et al, 2021); and Youtube (Albahlal, 2019) were among the learning media in the mobile application used by researchers to support the effectiveness of English learning process based on the teachers' perspectives. Moreover, most of the previous studies above researched the teachers' views at the Senior High School level (e.g., Albahlal, 2019;Nsabayezu et al, 2020;Sanjaya et al, 2021) and at the University level (e.g., Nguyen & Yukawa, 2019;Suryaman et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…As an instance, zoom meeting is effective to employ on teaching variety of subjects such as grammar (Octaviani, 2021), speaking (Putri & Suryaman, 2022), and writing (Erna et al, 2022) and other aspects (Helda & Zaim, 2021;Mu'awanah & Sumardi;Suparno, 2021). In addition, EFL lecturers must also be responsible for making creative teaching methods through Zoom Video Conferencing to achieve learning outcomes (Sanjaya, Fitri, & Hadiyatulloh, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In the other hand, the teachers also found several problems when teaching online using Zoom Cloud Meeting. Teachers have limited time to organize classes when using Zoom Cloud Meeting (Sanjaya, Fitri, & Hadiyatulloh, 2021). Then, Teachers also experience difficulties monitoring student progress (Gunawan, Kristiawan, Risdianto, & Monicha, 2021).…”
Section: Introductionmentioning
confidence: 99%